The Success Factors in ‘Hotel 626’ (2008) Forgotten Horror Advergame: A Content Analysis - Fatiya, Tiara; Humaira, Pocut (Jurnal Media dan Komunikasi, 2025)
This study analyzes the effectiveness of "Hotel 626" (2008), a browser-based horror advergame for Doritos Late Night, by applying Mona Jami Pour's (2020) success factors. Despite its advertising purpose, the game achieved significant viral reach and emotional impact without overt product placement, a unique approach for its time. Employing a qualitative and historical methodology, this research examines player reactions through online reviews and archived media, alongside historical marketing contexts. Findings indicate "Hotel 626" excelled by crafting an immersive horror narrative through innovative game design, effectively matching player personality with the horror genre, subtly integrating the brand through time-restricted access, and leveraging accessible technical factors for deep immersion. This analysis positions "Hotel 626" as an early and influential example of horror-themed advergames, demonstrating how compelling storytelling and interactive engagement can serve as potent, subtle marketing tools.